Impact of RAS, BRAF mutations and microsatellite status in peritoneal metastases from colorectal cancer treated with cytoreduction + HIPEC: scoping review - Zucchini, Valentina; D’Acapito, Fabrizio; Rapposelli, Ilario Giovanni; Framarini, Massimo; Di Pietrantonio, Daniela; Turrini, Riccardo; Pozzi, Eleonora; Ercolani, Giorgio (International journal of hyperthermia, 2025)
Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) has shown survival benefits in select patients with peritoneal metastases (PM) from colorectal cancer (CRC). Molecular alterations, particularly RAS/BRAF mutations and Microsatellite Instability (MSI), play crucial roles in prognostic stratification and treatment planning, influencing both disease-free survival (DFS) and overall survival (OS). This scoping review evaluates the prognostic role of MSI and RAS/BRAF mutations in patients with PM-CRC treated with CRS-HIPEC. A literature search was conducted across several databases to identify papers published between 2000 and September 2024. We selected 18 publications that considered DFS and OS as primary or secondary outcomes in patients with RAS/BRAF mutations and MSI following CRS-HIPEC treatment. Studies involving appendiceal cancer, peritoneal disease from non-CRC, pediatric patients, or subjects not treated with CRS-HIPEC were excluded. Most studies suggest that RAS and BRAF mutations have a negative influence on survival outcomes. While inconsistencies exist, RAS mutations are generally associated with worse DFS. Specific KRAS subtypes such as KRASMUT2 or KRAS G12V and the BRAF V600 variant correlate with poorer prognosis. MSI status appears to attenuate the adverse effects of RAS/BRAF mutations on survival, although conflicting data persist. RAS and BRAF mutations correlate with poorer outcomes in PM-CRC, underscoring the need for mutation-informed strategies to refine HIPEC and systemic therapies. Recognizing subtypes may improve patient selection for CRS-HIPEC, optimizing both local disease control and long-term survival. Future research should incorporate these molecular profiles to enhance therapeutic decision-making and better address this challenging condition.